Socio-Economic and Cultural Influence on Vitamin A Intake of Lactating Mothers in Ngaoundere Cameroon - Damndja Ngaha, W.; N. Fombang, Edith; Aba Ejoh, R. (Journal of Nutritional Therapeutics, 2016)
Background: Vitamin A deficiency (VAD) is a widespread public health problem in developing nations affecting greatly pregnant and lactating women. The intake of Vitamin A rich foods highly recommended to reduce the prevalence in these vulnerable groups are greatly influenced by the level of education, geographic origin and differences in food habits. Aims of the Study: To evaluate the Influence of socio-economic, cultural, geographic origin, and demographic factors on vitamin A (VA) intake of lactating mothers in Ngaoundere, Cameroon. Method: A total of 100 lactating mothers attending pediatric consultations at four major health structures in Ngaoundere were involved in the survey. A questionnaire was used to get information on socio-economic, cultural, demographic factors, geographic origin, anthropometric parameters and culinary practices. Dietary intake was assessed using a 24-hour dietary recall method. Meals potentially rich in VA consumed by these women were collected, their carotenoids contents quantified and VA activity determined. Results: Average VA intake of lactating women of Northern origin was significantly (p< 0.05) lower (595.2±60.4μg/day) than that of women of Southern origin (737.6±55.6μg/day), although both were below the recommended intake of 850μg/day. VA intake was also higher in the more educated women. Marital status, number of children, age of the mother and body mass index did not significantly influence the daily VA intake of the women. Lactating women of Northern origin, with three or more children and having no formal education, are more at risk of acute VA Deficiency. Conclusion: While the level of education influenced the VA intake in lactating women from the Northern Region, the age of the baby influenced those from the Southern Region.